2009
DOI: 10.1097/jcp.0b013e3181929f7a
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Drug Prescription and Risk of Abnormal Bleeding

Abstract: This study assessed the risk of any bleeding abnormalities, including the risk of gastrointestinal bleeding, associated with antidepressant exposure. We used a case-control methodology. Case patients were individuals admitted with a diagnosis of abnormal bleeding. Control subjects were individuals admitted on the same date without evidence of abnormal bleeding. During the study period, 11,025 case patients were admitted for bleeding abnormalities (matched with 21,846 eligible control subjects), and 1008 were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…160 In the absence of trials of sufficient size to identify differences in rare adverse outcomes, studies examining associations between antidepressant use and GI bleeding have been largely confined to cohort studies [24][25][26] and case-control studies. 27,[161][162][163] Whereas some studies have found an increased risk of GI bleeds to be associated with antidepressant use, 24,27,161 others have found no evidence for an effect. 25,163 There is conflicting evidence as to whether 25,26,162 or not 27 that risk is increased in the presence of NSAID use.…”
Section: Upper Gastrointestinal Bleedsmentioning
confidence: 97%
See 1 more Smart Citation
“…160 In the absence of trials of sufficient size to identify differences in rare adverse outcomes, studies examining associations between antidepressant use and GI bleeding have been largely confined to cohort studies [24][25][26] and case-control studies. 27,[161][162][163] Whereas some studies have found an increased risk of GI bleeds to be associated with antidepressant use, 24,27,161 others have found no evidence for an effect. 25,163 There is conflicting evidence as to whether 25,26,162 or not 27 that risk is increased in the presence of NSAID use.…”
Section: Upper Gastrointestinal Bleedsmentioning
confidence: 97%
“…Among adults admitted to hospital, a modest increased risk of GI bleeding was found with antidepressant use, but this was restricted to the group of other antidepressant drugs rather than TCAs or SSRIs. 161 A case-control study found that SSRIs overall were associated with an increased risk of upper GI tract bleeding, and also found a particularly increased risk for venlafaxine. 162 In a study of medication data, combined use of SSRIs and NSAIDs strongly increased the risk of GI adverse effects.…”
Section: Upper Gastrointestinal Bleedsmentioning
confidence: 99%
“…Barbui et al in a case-control study also found a modestly increased risk of gastrointestinal (GI) bleeding with usage of SSRIs, but no increased risk with tricyclic antidepressants. They showed that other antidepressants (including mianserin, trazodone, and venlafaxine) were associated with a statistically significant increased risk of GI bleeding [11]. Elderly patients are at greater risk for bleeding sequelae [5], as well as those who take agents with a higher degree of serotonin reuptake inhibition [12,13] ( Tables 5, 6).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported bleeding complications associated with the use of Selective Serotonin Reuptake Inhibitors (SSRIs) [13][14][15][16]. In contrast, Serotonin-Norepinephrine Reuptake Inhibitors (SNRIs) with a similar mechanism of action as sibutramine, generally are not associated with increased bleeding risks.…”
Section: Sibutraminementioning
confidence: 99%